Analisis Literatur tentang Efektivitas Media Berbasis Teknologi dalam Menstimulasi Kemampuan HOTS Siswa di Sekolah Dasar - Nafi'ah, Jamilatun (Auladuna: Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The use of technology-based media in learning has become a necessity in the digital era of 5.0. Data from the World Economic Forum (2020) in the Future of Jobs Report 2020 Geneva states that 50% of future jobs will require critical thinking and complex problem-solving skills. This necessitates preparation for teachers to enhance students' higher-order thinking skills (HOTS). This study aims to examine the effectiveness of technology-based media on students' HOTS. This study uses a literature review approach guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) diagram to select relevant literature. The analysed articles focus on technology/digital-based media and students' HOTs in primary schools published between 2020 and 2025. Literature searches were conducted using Google Scholar and Research Gatesinta. From the screening results, five main articles were identified that discussed the use of digital media such as Powtoon, Wordwall, Proprofs, and interactive PowerPoint in developing HOTs. The synthesis of findings indicates that digital media that are visual, interactive, and flexible can enhance learning interest, student engagement, and analytical, evaluative, and creative skills in line with the revised Bloom's Taxonomy. The success of digital media utilisation is significantly influenced by teacher readiness, digital literacy, and infrastructure support. Therefore, the integration of technology-based media with active and constructivist learning approaches is essential in stimulating students' HOTS abilities.